2015
DOI: 10.1128/jvi.00817-15
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiratory Tract Infection of the Ferret by 2009 H1N1 Pandemic Influenza A Virus Triggers Biphasic, Systemic, and Local Recruitment of Neutrophils

Abstract: Infection of the lower respiratory tract by influenza A viruses results in increases in inflammation and immune cell infiltration in the lung. The dynamic relationships among the lung microenvironments, the lung, and systemic host responses during infection remain poorly understood. Here we used extensive systematic histological analysis coupled with live imaging to gain access to these relationships in ferrets infected with the 2009 H1N1 pandemic influenza A virus (H1N1pdm virus). Neutrophil levels rose in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 108 publications
2
23
0
Order By: Relevance
“…In the ferret model, we have shown that the neutrophils become concentrated at specific foci in the lungs coincident with influenza-positive epithelium and the expression of chemoattractant chemokine genes (22). Neutrophil chemotaxis in humans is thought to be mediated by many factors, such as the chemokine CXCL8, cytokines IL-1 and TNFα, and complement C5a (145, 147, 148).…”
Section: Neutrophils In Iav Course Of Diseasementioning
confidence: 99%
“…In the ferret model, we have shown that the neutrophils become concentrated at specific foci in the lungs coincident with influenza-positive epithelium and the expression of chemoattractant chemokine genes (22). Neutrophil chemotaxis in humans is thought to be mediated by many factors, such as the chemokine CXCL8, cytokines IL-1 and TNFα, and complement C5a (145, 147, 148).…”
Section: Neutrophils In Iav Course Of Diseasementioning
confidence: 99%
“…12 Streptococcus pneumonia- induced alveolar infections can increase alveolar permeability and leukocyte accumulation and decrease surfactant protein D. 43 The 2009 H1N1 pandemic influenza infection also increased neutrophil levels throughout the alveolar space and enhanced inflammation and immune cell infiltration into the lung. 44 Investigations of host–pathogen interactions in the alveolar space will contribute to our understanding of lung diseases such as ALI/ARDS. However, the pulmonary alveoli that are located at the terminal ends of the distal airways are inaccessible to in vivo functional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, H1N1 pandemic flu of 1918 was both highly transmissible as well as virulent, while the 2009 H1N1 was highly transmissible but had moderate virulence. As opposed, H5N1 and H7N9 have low transmissibility but high virulence [11].…”
Section: Pathogenesismentioning
confidence: 99%